Impact of early antiviral therapy on SARS-CoV-2 clearance time in high-risk COVID-19 subjects: A propensity score matching study - Marta Colaneri; Federico Fama; Federico Fassio; Darcy Holmes; Giovanni Scaglione; Chiara Mariani; Lucia Galli; Alessia Lai; Spinello Antinori; Andrea Gori; Agostino Riva; Monica Schiavini (International Journal of Infectious Diseases)
Background: Effective treatments for COVID-19 are needed to mitigate disease progression and reduce the burden on healthcare systems. This study investigates the impact of early treatments on SARS-CoV-2 viral shedding duration among high-risk individuals with mild symptoms. Methods: A single-center, retrospective observational study was conducted at Luigi Sacco Hospital in Milan from December 2021 to March 2023. Hospitalized and nonhospitalized adults with a confirmed SARS-CoV-2 infection and at high-risk of disease progression were enrolled. Unadjusted and adjusted negative binomial regression models and a Random Forest regression model were performed before and after matching subjects based on their propensity of being treated or not. Results: Results from 518 subjects (428 treated and 90 untreated) revealed a significant reduction in SARS-CoV-2 viral shedding duration among those who received early treatment compared to untreated individuals. Propensity score matching and multivariable regression analyses confirmed this finding. Early treatment significantly reduced the risk of COVID-19-related hospitalization and pneumonia development. Subgroup analysis identified COPD as a potential factor influencing effectiveness of early treatments. Conclusions: Early treatments play a crucial role in reducing SARS-CoV-2 viral shedding and preventing disease progression among high-risk individuals. Shorter viral shedding duration also contributes to improved healthcare resource utilization and infection control measures.